2011
DOI: 10.1007/s11033-011-1035-4
|View full text |Cite
|
Sign up to set email alerts
|

CREB-binding protein silencing inhibits thrombin-induced endothelial progenitor cells angiogenesis

Abstract: Endothelial progenitor cells (EPCs) are known to promote neovascularization in ischemic diseases. Recent evidence from our group suggested that CREB-binding protein (CBP) plays an important role in thrombin-induced EPCs migration. However, whether CBP could regulate EPCs angiogenic properties is unknown. In the present study, we investigated whether CBP silencing could inhibit thrombin-induced EPCs angiogenesis. EPCs isolated from the bone marrow of Sprague-Dawley rats were cultured and identified, and then we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…cAMP response element-binding protein (CREB) and CREB-binding protein (CBP)/p300 play critical roles in epithelial tumorigenesis 117 . CREB is a transcription factor, whose signaling is implicated in the promotion of tumor progression, growth stimulation, apoptotic resistance, and the support of angiogenesis 118 , 119 . Li et al reported that activation of the CREB signaling pathway upregulates FSCN1 expression in breast adenocarcinoma, head and neck squamous cell carcinoma, and lung adenocarcinoma cells, leading to enhanced cancer cell invasion in vitro and tumor metastasis in vivo 120 .…”
Section: The Mechanisms Underlying Aberrant Fscn1 Expression In Cancermentioning
confidence: 99%
“…cAMP response element-binding protein (CREB) and CREB-binding protein (CBP)/p300 play critical roles in epithelial tumorigenesis 117 . CREB is a transcription factor, whose signaling is implicated in the promotion of tumor progression, growth stimulation, apoptotic resistance, and the support of angiogenesis 118 , 119 . Li et al reported that activation of the CREB signaling pathway upregulates FSCN1 expression in breast adenocarcinoma, head and neck squamous cell carcinoma, and lung adenocarcinoma cells, leading to enhanced cancer cell invasion in vitro and tumor metastasis in vivo 120 .…”
Section: The Mechanisms Underlying Aberrant Fscn1 Expression In Cancermentioning
confidence: 99%
“…Activation of PGC-1α also increased the expression of hypoxia-inducible genes, including HIF-1α [ 117 ]. CBP increased the transactivation of NF-κB and its target genes, including VEGF, in endothelial progenitor cells [ 118 ]. PPARγ stimulates the expression of VEGFR2 and promotes angiogenesis in endothelial cells [ 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…RSK2 is a Ser/Thr kinase that regulates cell proliferation, cell survival and cycle by phosphorylating cAMP response element binding (CREB) proteins ( 62 64 ). As a transcription factor, CREB participates in the signal pathway related to promoting tumor progression, stimulating growth, giving apoptosis resistance and promoting angiogenesis ( 65 , 66 ). Li et al.…”
Section: Fascin-1 and Non-small Cell Lung Cancermentioning
confidence: 99%